Soil Erosion: Types and Their Mechanism - Telkar, S. G.; Solanki, Shivendu Pratap Singh; Dey, Joy Kumar; Kant, Kamal (International Journal of Economic Plants, 2015)
Soil erosion is a universal phenomenon. Out of the 328.7 m ha of India’s geographical area about 175 m ha (53.3%) is subjected to soil erosion and some kind of land degradation. Soil erosion is one form of soil degradation along with soil compaction, low organic matter, and loss of soil structure, poor internal drainage, salinization, and soil acidity problems. This other forms of soil degradation, serious in them; usually contribute to accelerated soil erosion. There are several factors responsible for soil erosion. Soil conservation is an essential practice for getting good crop production from all regions especially from arid and semi-arid areas. In arid and semi-arid regions these two factors are major indicators of soil quality. Low soil moisture leads to erosion by wind and excess water leads to leaching of nutrients. So, soil erosion is the major threat to dry regions of the country. This article reviews the various types of soil erosion and mechanisms behind. This information is essential for adopting suitable soil conservation strategy.